Um ambiente para simulação da gestão de projetos de software - Leite, Danilo Rangel Arruda (2013)
Inadequate implementation of management techniques in software projects often leads to failure and possible cancellation of a project. One possible cause is the lack of a better understanding of its key practices. The use of simulators in training can have a high power motivation may present benefits compared to other traditional forms of learning. This paper aims to design and development of an educational game for teaching project management software in undergraduate courses in computing. As validation of the proposal, the game was submitted to a group of undergraduate course in computer science, having complied with the initial expectation of aid in teaching-learning of the discipline.